Wajah Islam Nusantara: Menelusuri Ciri Khas Akulturasi Budaya Muslim Asia Tenggara - Ahmad Albasith (Jurnal Global Futuristik, 2026)
This study traces the historical and sociological processes of acculturation between Islamic teachings and local cultures in Southeast Asia, which has produced an adaptive, moderate, and inclusive civilization known as Islam Nusantara. Employing a descriptive-analytical qualitative method with a historical-sociological approach, this research relies on library research analyzing academic literature and historical records. The findings indicate that the spread of Islam in this region occurred peacefully through trade and Sufi cultural approaches, subsequently giving rise to a distinct typology of cultural integration within Malay and Javanese societies. This acculturation manifests physically in the architectural aesthetics of ancient mosques with odd-numbered tiered roofs, and socially through the preservation of indigenous traditions. Various traditions—such as the Buang-buang ritual to ward off misfortune, the oral art of Dzikir Nazam, and the Saprahan banquet tradition—have retained their functions, yet their core essence has been sublimated with the values of Tawhid (monotheism) and egalitarian equality. Through the adept application of ushul al-fiqh (Islamic jurisprudence) approaches based on 'urf (local customs) and maslahah (public interest), Nusantara scholars were able to harmoniously weave sharia doctrines with customary traditions. In conclusion, Islam Nusantara proves itself to be not merely a religious entity, but a civilizational force that promotes the values of moderation (wasathiyyah) while simultaneously serving as a soft power in cultural diplomacy to mitigate the threat of global extremism.